FERGANA REGIONAL PUPPET THEATER: ITS DEVELOPMENT, RELEVANCE AND PLACE IN MODERN CULTURE - Abbosjon Umurzoqov Shavkat o‘g‘li; Scientific Director U. Karabayev (Bright Mind Publishing, 2025)
The article discusses the historical formation of the Fergana regional puppet theater, its role in the current theatrical space of Uzbekistan, and its current tasks based on a scientific approach. In particular, the role of theatrical art in the harmonious upbringing of the younger generation, its importance in promoting national culture, and its activity in international cooperation are analyzed.
Keywords: puppet theater, theatrical art, young generation, national culture, Fergana, current problem, international cooperation.